UPAYA PENINGKATAN PRESTASI ATLET MELALUI LITERASI GIZI - NOORDIA, ANNA (Ordik, 2013)
Nutrition’s literacy (literacy nutrition) can be defined as the capacity to obtain, process, and understand basic nutrition information needed to make a decision right diet. Nutrition plan has an urgent role in coaching athletes achievements. The fulfillment of balance nutrition for an athlete is one factor that affects athlete achievement. Energy requirement for athlete is calculated from individual requirements. The latest nutrition and school health research provides data indicating a correlation between quality nutrition education and the selection of foods for a healthy diet   Keywords: literasi gizi, prestasi olahraga, gizi olahraga